How dividend policy and leverage influence the stock price volatility - Bong, Hui Hian (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study aims to investigate the stock price volatility's trend of 470 non-financial listed firms in Malaysia from 2005 to 2010. Besides, the relationship of stock price volatility with dividend policy (payout ratio and dividend yield), leverage and firm size also been examined. The stock price in Malaysia shows its volatile trend during the financial crisis period. However, at post-crisis period, the trend is less volatile among the Malaysian's firms. In overall, the findings show that the payout ratio and leverage are tending to signaling hypothesis theory and the pecking order theory respectively. At the pre-crisis period (2005 to 2007), the dividend yield supports the signaling hypothesis theory; while leverage has no impact on stock price volatility which reflected Modigliani and Miller Theory (M&M II). During the post-crisis period (2008 to 201 0), the payout ratio is insignificant as proposed byModigliani and Miller Theory~' (M&M I); whereas the levera~e follows the pecking order theory showing a significant positive relationship with the stock price volatility.